2021
DOI: 10.3390/cells10020382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpha-Glucosyl-Hesperidin Consumption on Lens Sclerosis and Presbyopia

Abstract: Presbyopia is characterized by a decline in the ability to accommodate the lens. The most commonly accepted theory for the onset of presbyopia is an age-related increase in the stiffness of the lens. However, the cause of lens sclerosis remains unclear. With age, water microcirculation in the lens could change because of an increase in intracellular pressure. In the lens, the intracellular pressure is controlled by the Transient Receptor Potential Vanilloid (TRPV) 1 and TRPV4 feedback pathways. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Work in an animal (mouse) model has investigated the role α-glucosyl-hesperidin (G-Hsd) may play in maintaining lens antioxidant levels to prevent cataract formation and presbyopia development. Building on a previous study reporting that G-Hsd prevents nuclear cataract formation in 37 weeks old mice,76 the same laboratory demonstrated that lens elasticity retains a higher level of malleability when compared with those mice administered orally with both 1 % and 2 % G-Hsd 77. The mechanism appears to be mediated through an affected distribution of Transient Receptor Potential Vanilloid 1 feedback pathways that control lens intracellular pressure 78.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 91%
See 1 more Smart Citation
“…Work in an animal (mouse) model has investigated the role α-glucosyl-hesperidin (G-Hsd) may play in maintaining lens antioxidant levels to prevent cataract formation and presbyopia development. Building on a previous study reporting that G-Hsd prevents nuclear cataract formation in 37 weeks old mice,76 the same laboratory demonstrated that lens elasticity retains a higher level of malleability when compared with those mice administered orally with both 1 % and 2 % G-Hsd 77. The mechanism appears to be mediated through an affected distribution of Transient Receptor Potential Vanilloid 1 feedback pathways that control lens intracellular pressure 78.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 91%
“…Building on a previous study reporting that G-Hsd prevents nuclear cataract formation in 37 weeks old mice, 76 the same laboratory demonstrated that lens elasticity retains a higher level of malleability when compared with those mice administered orally with both 1 % and 2 % G-Hsd. 77 The mechanism appears to be mediated through an affected distribution of Transient Receptor Potential Vanilloid 1 feedback pathways that control lens intracellular pressure. 78 Although these data await replication in humans, the findings suggest that G-Hsd is a potential oral compound to prevent presbyopia and cataract formation.…”
Section: The Patient Experience Of / Journey Through Presbyopiamentioning
confidence: 99%
“…Moreover, TRPV1 and/or TRPV4 in peripheral fiber cells of the lens alter their membrane trafficking by accommodating changes, meaning that TRPV channels located in the cytoplasm comprise a protein pool that meets physiological needs and accommodates changes. The authors previously reported that treatment with oral a-glucosyl hesperidin, which is Hst derivatives with a water solubility ~10,000 times higher than that of Hst, altered TRPV4 localization in the peripheral fibre cells of the lens to control water microcirculation ( 20 ). Additionally, oral treatment ameliorated lens fluid influx and osmotic imbalance in the lenses of individuals with diabetes and cataracts ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of lens elasticity. lens elasticity was measured using SoftMeasure HG1003-Sl (Horiuchi electronics co., Ltd.) as previously described (19,20). Briefly, the lens was mounted soon after euthanasia and then a load was applied to the top of the lens to measure the force and indentation displacement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation